Winter of the world - Follett, Ken (Follett, Ken. Century trilogy, 2012)
Continues the stories of five interrelated families who struggle with social, political, and economic turmoil in the mid-twentieth century, during which they witness the rise of Nazi Germany, the Spanish Civil War, and the horrors of World War II.